Novel Coronavirus (Covid-19): It’s Implication for Improving Discipline, Manner, and Skills - Chhatkuli, Shyam Bahadur; Ariyal, Uttam (Journal of Advanced Academic Research, 2020)
The research explores the implication of difficulties including lockdown caused by COVID-19 virus in improving discipline, manner, and skills for the development of society for independency. It studies a very backward village, Aambhanjyang, a village developing towards the city and a provincial capital city. It has not only the dark side by COVID-19 virus but also has a bright side for social development. With the study of its nature, human gains skills, develop a manner of self-discipline, and does the correction in culture. The changes may bring the dependent society into an independent society. The people from all the three types of location were not used to for the habits which prevent several types of communicable diseases passing from each other. It can be concluded that the difficult circumstances compel/opportune human to exist and combat with the new problems. Findings help society to be skilled in health care, mannered in behaving with each others, skilled for performing good and useful habits. Because of the changes, the skills, manner, habits make people disciplined and the discipline changes into tradition and finally the tradition become culture.